The Politicized Pandemic: Ideological Polarization and the Behavioral Response to COVID-19 - Gianluca Grimalda; Fabrice Murtin; David Pipke; Louis Putterman; Matthias Sutter (Institute of Labor Economics (IZA), 2022)
We investigate the relationship between political attitudes and prosociality in a survey of a representative sample of the U.S. population during the first summer of the COVID-19 pandemic. We find that an experimental measure of prosociality correlates positively with adherence to protective behaviors. Liberal political ideology predicts higher levels of protective behavior than conservative ideology, independently of the differences in prosociality across the two groups. Differences between liberals and conservatives are up to 4.4 times smaller in their behavior than in judging the government's crisis management. This result suggests that U.S. Americans are more polarized on ideological than behavioral grounds.
Keywords: D01; D72; D91; I12; I18; H11; H12; 330; health behavior; worries; polarization; ideology; trust in politicians; COVID-19; prosociality